2017
DOI: 10.1055/s-0043-101909
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Garmin Vector Power Meter in Laboratory and Field Cycling

Abstract: To assess the validity and reliability of the Garmin Vector against the SRM power meter, 6 cyclists completed 3 continuous trials at power outputs from 100-300 W at 50-90 rev·min and a 5-min time trial in laboratory and field conditions. In field conditions only, a 30-s sprint was performed. Data were compared with paired samples t-tests, with the 95% limits of agreement (LoA) and the typical error. Reliability was calculated as the coefficient of variation (CV). There was no significant difference between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…The results of this study are comparable to studies published using earlier versions of the Garmin Vector pedals with a CV of 2.0% for the V1 pedals reported between 150 W and 350 W. 7 Additionally, these results are similar to the reported CV of ∼3.0% of the V2 pedals when tested between 100 W and 300 W. 8 The results of the present study are also comparable to other pedal-based systems with a CV of <6.3% observed for the PowerTap P1 pedals when tested at sub-maximal power outputs and during all-out sprinting. 11 Additionally, the TEM of 75.8 W observed during all-out sprinting is similar to the PowerTap P1 pedals (75.1 W).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study are comparable to studies published using earlier versions of the Garmin Vector pedals with a CV of 2.0% for the V1 pedals reported between 150 W and 350 W. 7 Additionally, these results are similar to the reported CV of ∼3.0% of the V2 pedals when tested between 100 W and 300 W. 8 The results of the present study are also comparable to other pedal-based systems with a CV of <6.3% observed for the PowerTap P1 pedals when tested at sub-maximal power outputs and during all-out sprinting. 11 Additionally, the TEM of 75.8 W observed during all-out sprinting is similar to the PowerTap P1 pedals (75.1 W).…”
Section: Discussionsupporting
confidence: 89%
“…6 In contrast, studies suggested that the second version of the Garmin Vector pedals (V2) are comparable to the SRM Powermeter, with no significant difference in power output during sub-maximal cycling observed; however, significant differences were seen during sprint cycling. 8 The P1 pedals have also been reported to demonstrate excellent levels of agreement when compared to a Wattbike Pro cycle ergometer during a 16.1 km time-trial, with an intra-class correlation of >0.8. 9 Both the V2 and P1 pedals have demonstrated acceptable test-retest reliability during sub-maximal cycling.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Instead, they were either relying on an estimate based on body mass [ 48 , 82 ] for untrained participants, or the subjective examination of training data from trained participants [ 45 ]. It is noteworthy that readily available commercial power meters are now commonplace amongst trained cyclists with many systems being validated against laboratory ergometers [ 83 , 84 , 85 , 86 ], and as such careful examination of recent training and race history should provide estimates of CP and preferred cadence at least as valid as the 50% delta between GET and 2max derived from preliminary tests [ 12 , 67 ].…”
Section: Methods For Determining Critical Power and W′mentioning
confidence: 99%
“…Although instrumented pedals have been used in biomechanics laboratories for many years [3][4][5][6], their availability as commercial products is more recent. These commercial systems have shown to be accurate in comparison with the SRM power meter, often used as a gold standard [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%